Security in Schools : Its Effect on Students. - Phaneuf, Shannon Womer (Criminal justice (LFB Scholarly Publishing LLC), 2009)
Millions of dollars are spent each year improving school security, but little has been done to assess the influence of these strategies on school violence or student fear. Phaneuf examined the influence of school security practices on student fear, student bonding, and school climate in a sample of secondary schools. Her results indicated that the use of security practices in schools did not influence levels of student fear or bonding. Several school- and community-level variables were better predictors of student fear and bonding than was the use of school security strategies. Among these var.